Qur'an Story Telling Method to Improve Children's Arabic Language in Muhammadiyah 07 Integrated Elementary School Pekanbaru - Eka Rinor Maya; Arbi Yasin (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the efficiency of narrative style/story telling of the Qur'an to support the improvement of students' Arabic vocabulary and also improve children's social behavior through stories conveyed through learning. This study used a random sampling technique with a sample of ten (10) students from SD Muhammadiyah 07 Terpadu Pekanbaru, by combining quantitative and qualitative methods. The data sources are from the results of observations, interviews, documentation, and learning stages I-IV, as well as the results of Classroom Action Research (CAR) using the Kurt Lewin model (1946). The findings of the study indicate that students at SD Muhammadiyah 07 Terpadu Pekanbaru Arabic through story telling stories from the Qur'an can significantly improve children's Arabic, namely the increase in mufrad or Arabic vocabulary. And the latest findings in this study are that story telling stories from the Qur'an can improve social attitudes and behavior, empathy, and cognitive growth of students of SD Muhammadiyah 07 Terpadu class III Pekanbaru based on the characteristics of the Prophet such as Siddiq, Amanah, Fathanah and Tabligh and moral values in the story such as being patient, always praying and thinking well